The Vivified Sacrificial Rites as the Site of Conflation of Man and Animal in Adele Wiseman’s "The Sacrifice" - Tazbir, Jędrzej (Analyses/Rereadings/Theories: A Journal Devoted to Literature, Film and Theatre, 2019)
The article juxtaposes two explanations of the ancient phenomenon of sacrifice, one of which, formulated by René Girard, emphasizes the aspects of scapegoating and transference of people’s violent inclinations, while the other, developed by Jonathan Klawans and focused on the ancient Israeli sacrificial customs, attributes chief significance to the notions of purity, defilement, and achieving the state of imitatio Dei by the offerer. Though these explanations are at odds in many respects, with Klawans being vocally critical of Girard’s approach, the article seeks to present both of them as applicable to the context of a contemporary sacrifice depicted in Adele Wiseman’s novel, The Sacrifice. Its protagonist, the article argues, finds a way of blending these two orders together largely by the use of the mental figure of the animal, the projection of which onto his victim allows him to perceive her in dualistic manner, as simultaneously sacred and wicked. In the light of this, the ostensibly morally sanctioned practice of ancient Abrahamic sacrifice is shown to contain an unaccounted for potential to instigate ruinous acts, and the figure of the animal, within a situation characterized by the blurring of boundaries and distinctions, with which a sacrificial crisis is unalterably associated, attains an ambiguous, if not sinister, significance.